2000
DOI: 10.1074/jbc.m000312200
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced Activation of Protein Kinase CK2 by Direct Interaction with p38 Mitogen-activated Protein Kinase

Abstract: Protein kinase CK2 has been implicated in the regulation of a wide range of proteins that are important in cell proliferation and differentiation. Here we demonstrate that the stress signaling agents anisomycin, arsenite, and tumor necrosis factor-␣ stimulate the specific enzyme activity of CK2 in the human cervical carcinoma HeLa cells by up to 8-fold, and this could be blocked by the p38 MAP kinase inhibitor SB203580. We show that p38␣ MAP kinase, in a phosphorylation-dependent manner, can directly interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 33 publications
(18 reference statements)
5
113
0
Order By: Relevance
“…4A). Activated p38-MAPK associates with CK2 to enhance phosphorylation of p53 at Ser392 (31)(32)(33). Therefore, we investigated whether p38-MAPK was involved in the The plot represents data from at least three independent experiments AE SEM.…”
Section: P38-mapk Is Required For Signaling During T-type Ca 2þ Channmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Activated p38-MAPK associates with CK2 to enhance phosphorylation of p53 at Ser392 (31)(32)(33). Therefore, we investigated whether p38-MAPK was involved in the The plot represents data from at least three independent experiments AE SEM.…”
Section: P38-mapk Is Required For Signaling During T-type Ca 2þ Channmentioning
confidence: 99%
“…In particular, upon UV-induced DNA damage or osmotic shock, p38-MAPK phosphorylates p53 at Ser46 (29) or Ser33 (30), thus stabilizing p53. Moreover, UVinduced DNA damage activates p38-MAPK to activate casein kinase 2 (CK2), which in turn also phosphorylates p53 at Ser392, increasing p53 transcriptional activity (31)(32)(33). Thus, p38-MAPK supports increased p53 levels and activity.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed investigations of CK2 in yeast and in mammalian cells have further demonstrated that CK2 is required for cell cycle progression with roles at di erent stages in the cell cycle including G1, G1/S and G2/M (Hanna et al, 1995;Pepperkok et al, 1991;Lorenz et al, 1993). A role for CK2 in cellular responses to various stresses including UV, anisomycin, arsenite, heat shock and TNFa has also recently emerged (Sayed et al, 2000;Ghavidel and Schultz, 2001;Keller et al, 2001;Gerber et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Serine 389 in mouse p53 is phosphorylated by casein kinase II and p38 MAP kinase after UV radiation but not IR (Kapoor and Lozano, 1998;Lu et al, 1998;Sayed et al, 2000;Keller et al, 2001). First, we determined if the mutant p53 S389A protein, expressed by the mouse embryonic fibroblasts (MEFs) from a mouse homozygous for the p53 S389A mutation, could not be phosphorylated at codon 389 after UV radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The extreme C-terminus of p53 is believed to function as a negative regulatory domain (Hupp and Lane, 1994a, b;Pellegata et al, 1995;Wiederschain et al, 2001). Serine 392 in human p53 (389 in mouse) is present in this region and is known to be modified only by ultraviolet (UV) radiation, but not g-radiation (IR), through phosphorylation by casein kinase II and p38 MAP kinase (Kapoor and Lozano, 1998;Lu et al, 1998;Sayed et al, 2000;Keller et al, 2001). Biologically, this modification is known to stabilize the p53 tetramer and enhance sequence-specific DNA-binding ability of p53 through a conformational change Lane, 1994a, 1995;Sakaguchi et al, 1997).…”
mentioning
confidence: 99%